On Sectional Curvatures of (ε)-Sasakian Manifolds - Rakesh Kumar; Rachna Rani; R. K. Nagaich (International Journal of Mathematics and Mathematical Sciences)
We obtain some basic results for Riemannian curvature tensor of (ε)-Sasakian manifolds and then establish equivalent relations among φ-sectional curvature, totally real sectional curvature, and totally real bisectional curvature for (ε)-Sasakian manifolds.